Primerjava športnih dejavnosti učencev iz Maribora in Novega Sada - Jančič, Jasmina; Planinšec, Jurij (Revija za elementarno izobraževanje, 2018)
Comparison of Sports Activities among Students from Maribor and Novi Sad. The main aim of the study was to determine the extent of physical activity among students from Maribor and Novi Sad, the nature of such activity and whether there is a difference in the physical activities of students from these cities. The study involved 100 students from Novi Sad and 102 students from Maribor, who attended the 4th, 5th, 6th and 7th grades of elementary schools, of which 96 were girls and 106 boys. In order to collect data, we used a survey questionnaire that students completed in their mother language. The data was processed with the SPSS 21 program, using the χ²-test and t-test. The results show that there are significant differences between students from Maribor and students from Novi Sad in attending physical activities at school, physical activities with the family and in unorganized physical activity. There was no significant difference in attendance at organized physical activities. We can conclude that students from Maribor are more physically active than are students from Novi Sad.DOI: 10.18690/rei.11.4.329-340.2018COBISS-ID: 24277512